Funkcjonowanie społeczne chorych na padaczkę = The social functioning of patients with epilepsy - Olejniczak, Dominik; Kowalczyk, Joanna; Staniszewska, Anna (Journal of Education, Health and Sport, 2016)
Olejniczak Dominik, Kowalczyk Joanna, Staniszewska Anna. Funkcjonowanie społeczne chorych na padaczkę = The social functioning of patients with epilepsy. Journal of Education, Health and Sport. 2016;6(1):118-128. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44833 http://ojs.ukw.edu.pl/index.php/johs/article/view/44833 https://pbn.nauka.gov.pl/works/696065 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 18.01.2016. Funkcjonowanie społeczne chorych na padaczkę The social functioning of patients with epilepsy Dominik Olejniczak, Joanna Kowalczyk, Anna Staniszewska Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny Katedra i Zakład Farmakologii Doświadczalnej i Klinicznej, Warszawski Uniwersytet Medyczny Autor do korespondencji: Dominik Olejniczak Warszawski Uniwersytet Medyczny Zakład Zdrowia Publicznego Ul. Banacha 1a, blok F, niski parter, p.39 02-097 Warszawa Streszczenie Wprowadzenie. Każda choroba, w szczególności przewlekła, niesie za sobą różnego typu obciążenia w codziennym życiu. Do chorób szczególnie wpływających na funkcjonowanie chorego w różnych sferach, należy padaczka. Jest to choroba cechująca się specyficzną naturą, kojarząca się z charakterystycznymi objawami, wymagająca długotrwałej terapii i nadal budząca szereg kontrowersji. Cel. Celem pracy było poznanie specyfiki funkcjonowania chorych na padaczkę w społeczeństwie, ze szczególnym uwzględnieniem obaw, dotyczących ich postrzegania przez innych. Materiał i metody. Narzędziem zastosowanym w badaniu był autorski kwestionariusz, natomiast zastosowaną techniką była ankieta, wypełniana w formie elektronicznej. Kwestionariusz zawierał pytania dotyczące choroby, trudności z nią związanych oraz metryczki. Badanie przeprowadzono w okresie grudzień 2014 - maj 2015 r. Do analizy wyników zakwalifikowano 116 kwestionariuszy (przy 4 odrzuconych). Wyniki. Aż 43,1% osób obawia się informować inne osoby o swojej chorobie; połowa respondentów (50%) obawia się wyjścia z domu, zaś 81% ankietowanych ma obawy związane z wystąpieniem kolejnego napadu, najczęściej z powodu możliwości doznania urazu (38%). Aż 62,1% osób odczuwało negatywne skutki przyjmowania leków przeciwpadaczkowych. Większość ankietowanych (78,4%) doświadczyła napadu w miejscu publicznym - tylko 47,4% osób otrzymało pomoc. Wnioski. Chorzy obawiają się wystąpienia napadów padaczkowych w miejscu publicznym, wzbudza w nich lęk wizja okaleczenia spowodowana nieuzyskaniem odpowiedniej pomocy. Chorzy spotkali się z negatywnymi opiniami na temat swojej choroby i być może z tego powodu mają problemy z informowaniem otoczenia o chorobie. Konieczne jest informowanie społeczeństwa o specyfice padaczki, włączając w to edukowanie w temacie podstawowych objawów napadu, oraz podstaw udzielania pomocy w razie napadu, w celu podniesienia jakości życia i poczucia bezpieczeństwa chorych. Słowa kluczowe: padaczka, obawy, funkcjonowanie społeczne. Abstract Introduction. Every disease, especially chronic, entails different types of loads in everyday life. To diseases particularly affecting the functioning of a patient in various spheres, to be epilepsy. It is a disease which is associated with characteristic symptoms requiring long-term therapy and still waking a number of controversies. Aim. The aim of the study was to investigate the specifics of functioning of patients with epilepsy in society, with particular emphasis on concerns about their perception by the public. Material and method. The method used in the study was the questionnaire, and the technique used was a survey, completed in electronic form. The questionnaire contained questions about the disease, problems related specifications. The study took place in the period December 2014 - May 2015. For the analysis of the results of the questionnaires were qualified 116 (from 4 rejected). Results. As many as 43.1% of people are afraid to inform others about their disease; half of the respondents (50%) are afraid to leave their homes, while 81% of respondents have concerns about the onset of another attack, mostly because of the possibility of injury (38%) As many as 62.1% of people felt the negative effects of antiepileptic medication. The majority of respondents (78.4%) experienced seizure at the site public - only 47.4% of people have received assistance. Conclusions. Patients fear of seizures in public, arouses fear in them a vision of injury caused by failure to obtain adequate assistance. Patients met with negative opinions about their disease and perhaps for this reason they have problems with ambient informing about the disease. It is necessary to inform the public about the specifics of epilepsy, including educating the topic of basic symptoms of the attack, and the basis for granting assistance in the event of an attack, in order to improve the quality of life and sense of security of patients. Key words: epilepsy, afraid, social functioning.